Pengaruh Kualitas Produk Dan Harga Terhadap Keputusan Pembelian Kosmetik Wardah Di Official Storewardah Pada E-Commerce Shopee - Anifa Purwaningsih; Hanuna Shafariah (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to examine the effect of product quality and Nprice of Wardah Cosmetics purchase decision in Official Store In the ecommerce shop. This research uses purposive sampling, the type of research used in this study is a quantitative method using SPSS software.Technique sampling used is the number of infinite population and sample of 130 respondents. The population of this study are consumers everb bought Wardah Cosmetics at the official Wardah store on Shopee ecommerce. Data collection techniques performed with spread the questionnaire respondents by using linear regression double. The resultsshowed that product quality significant effect on purchasing decisions with the level significance of 0.000 < 0.025 and the value of t count > t table 5.307 > 1.979). Price significant effect of 0.000 < 0.025 and the value of T xiii calculate > t table (5,657 > 1,979). Product quality and price simultaneously affect Purchase decisions with a significance level of 0.000 < 0.05 as well as the value of F count > F table (210383 > 3.07).